Peningkatan Kompetensi Aqidah Akhlak melalui Media Power Point Animation menggunakan Pembelajaran Direct Instruction - Wazzuriyah, Lola; Sari, Rita; Iqbal, Muhammad (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2021)
During the learning process, sometimes students feel bored and bored, one of the causes is the lack of innovation in classroom learning. So to overcome the boredom, then in this study used animation media from PowerPoint by using the Direct Instruction learning model. The purpose of this study is to look at the activeness of students' learning. The research method used is a type of classroom action research. The study was conducted in two cycles. The results of cycle 1 have not met the KKM that has been set, then the need for improvement in cycle II. The results obtained in cycle 1 are 60% while in cycle II the results obtained are 90%. So it can be concluded that the utilization of PowerPoint animation with direct instruction can improve students' learning competence in Aqidah Akhlak subjects in MIN 2 Aceh Tamiang.